COPYRIGHT PROTECTION FOR COMPUTER PROGRAMS, DATABASES, AND COMPUTER-GENERATED WORKS: IS ANYTHING NEW SINCE CONTU? - Miller, Arthur R. (Harvard Law Review)
Investigates the progress of U.S. court decisions with regard to copyright protection in relation to the prevalence of computer programs, electronic database and the use of artificial intelligence. Regulations imposed by the National Commission on New Technological Uses of Copyrighted Works; Provisions of the 1976 Copyright Act; Development of a framework for copyright laws.